Hacking Android : explore every nook and cranny of the Android OS to modify your device and guard it against security threats - Kotipalli, Srinivasa Rao; Imran, Mohammed A. (Packt Publishing, 2016)
"Hacking Android is a step-by-step guide that will get you started with Android security. You'll begin your journey at the absolute basics, and then will slowly gear up to the concepts of Android rooting, application security assessments, malware, infecting APK files, and fuzzing. On this journey you'll get to grips with various tools and techniques that can be used in your everyday pentests. You'll gain the skills necessary to perform Android application vulnerability assessment and penetration testing and will create an Android pentesting lab."--Resumé vydavatele
Obsahuje rejstřík
Keywords: Android (operační systém); mobilní operační systémy; počítačová bezpečnost; mobilní aplikace; Android (operating system); mobile operating systems; computer security; mobile applications; příručky; handbooks and manuals